China’s health service collaboration in the Guangdong-Hong Kong-Macao Greater Bay Area: barriers and next steps - Weidong Wu (Frontiers in Public Health)
Health service collaboration in the Guangdong-Hong Kong-Macao Greater Bay Area is crucial in addressing the growing healthcare demands driven by increasing migration and economic integration. This study highlights the significance of such collaboration in enhancing cross-border medical services and responding to the region’s evolving public health needs. Despite its potential benefits, several challenges impede effective collaboration, including the lack of mutual recognition of medical qualifications, limited interconnectivity of health information systems, and divergent regulatory frameworks that complicate service delivery across the regions. To mitigate these obstacles, the study advocates for the establishment of comprehensive regulatory alignment, which would ensure mutual recognition of healthcare professionals’ qualifications. Furthermore, the development of integrated platforms for information sharing and service regulation is essential for fostering effective cooperation in delivering health services.